A Retrospective Epidemiological Analysis of Microscopically Detected Babesiosis in Dogs of Southern Poland (2018–2022) - Olga Pawełczyk; Paulina Iwase; Bartosz Wierzba; Milena Kretschmer; Robert Wojtyczka; Krzysztof Solarz (Pathogens)
Babesia canis is the parasite responsible for a life-threatening disease for dogs in Central Europe, of which the main vector is the ornate dog tick—Dermacentor reticulatus. The objective of the presented study was to assess the prevalence of Babesia infection in dogs with clinical suspicion of babesiosis, which tested positive for B. canis from locations where there is no or very limited information about dog exposure to this pathogen. In order to confirm the presence of this protozoan, blood samples were collected from dogs treated in veterinary clinics with suspicion of canine babesiosis. The samples were sent for microscopic analysis to Vetlab, a commercial veterinary diagnostic laboratory, to confirm the diagnosis. Overall, 3032 dog blood samples from Southern Poland were examined between 1 August 2018 and 31 December 2022 at the Vetlab laboratory. A total of 282 (9.3%) samples were found to be Babesia-positive using Wright–Giemsa stain peripheral blood smears, with an increase in two periods per year—April and October. Among the five voivodships, from which the laboratory analyzed blood samples, the highest number of Babesia-positive samples came from Częstochowa (Silesia) and its surroundings. Moreover, Babesia protozoans occurred more frequently in blood smears of pure-breed rather than mixed-breed dogs. The obtained results showed that infections with large Babesia in dogs from Southern Poland (with a special indication for the Śląskie Voivodship) should be taken into consideration during the differential diagnosis of tick-borne diseases at veterinary clinics. The presented study increases the vigilance and awareness of veterinarians and dog owners in this region, where babesiosis was very rarely diagnosed until date.